Laser treatment of congenital esophageal stenosis and web at the upper esophageal sphincter - Özer Çakır, Özlem (Turkish Journal of Gastroenterology, 2019)
Cite this article as: Özer Çakır Ö. Laser treatment of congenital esophageal stenosis and web at the upper esophageal sphincter. Turk J Gastroenterol 2019; 30(9): 858-9.